IECON 2018 - 44th Annual Conference of the IEEE Industrial Electronics Society 2018
DOI: 10.1109/iecon.2018.8591074
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Traffic Flows with DSRC Technology: Field Trials and Performance Evaluation

Abstract: As traffic congestion becomes a huge problem for most developing and developed countries across the world, intelligent transportation systems (ITS) are becoming a hot topic that is attracting attention of researchers and the general public alike. In this paper, we demonstrate a specific implementation of an ITS system whereby traffic lights are actuated by DSRC radios installed in vehicles. More specifically, we report the design of prototype of a DSRC-Actuated Traffic Lights (DSRC-ATL) system. It is shown tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 24 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…Traffic Direction (DSRC) access technology was used in another study [5] to design a DSRC-Actuated Traffic Lights (DSRC-ATL) through a Computation Unit that runs a traffic signal control algorithm based on the messages sent from (DSRC OBU) of vehicles to roadside units (DSRC RSU). Research results demonstrated the poor ability of DSRC to support efficient and reliable V2X communications by revealing its poor performance in high vehicle density environments [6].…”
Section: Speedmentioning
confidence: 99%
“…Traffic Direction (DSRC) access technology was used in another study [5] to design a DSRC-Actuated Traffic Lights (DSRC-ATL) through a Computation Unit that runs a traffic signal control algorithm based on the messages sent from (DSRC OBU) of vehicles to roadside units (DSRC RSU). Research results demonstrated the poor ability of DSRC to support efficient and reliable V2X communications by revealing its poor performance in high vehicle density environments [6].…”
Section: Speedmentioning
confidence: 99%
“…The performance of a DSRC broadcast system in a high-density vehicle environment has been studied [13], yet the assumption was too ideal to be realistic-i.e., the number of vehicles within a vehicles communication range was kept constant. Another study proposed a DSRC-based traffic light control system [14], but it limited the applicability to the traffic lights only.…”
Section: Related Workmentioning
confidence: 99%
“…The performance of a DSRC broadcast system in a highdensity vehicle environment has been studied [16], yet the assumption was too ideal to be realistic, which means that the number of vehicles within a vehicle's communication range was kept constant. Another study proposed a DSRCbased traffic light control system [17], but it limited the applicability to the traffic lights only.…”
Section: ) Congestion In Dsrc Networkmentioning
confidence: 99%